2017
DOI: 10.1159/000487998
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrocurcumin Provides Neuroprotection in Experimental Traumatic Brain Injury and the Nrf2 Signaling Pathway as a Potential Mechanism

Abstract: The protective effect of tetrahydrocurcumin (THC) after experimental traumatic brain injury (TBI) has been demonstrated, as demonstrated by the inhibition of oxidative stress, mitochondrial dysfunction, and apoptosis. However, the mechanisms underlying this effect are still not well understood. This study was to investigate the neuroprotective effects of THC, and its potential mechanisms, in a rat model of TBI. To this end, rats were divided into 4 groups: the sham group, the TBI group, the TBI + vehicle (V) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Increased use of marijuana among Americans is coincided with its implication in emergency departments visits, motor vehicle collisions, and trauma [ 15 , 16 ]. THC has been associated with neuroprotective effects after TBI in several preclinical studies [ 17 , 18 ]. A 3-year retrospective review from a Level 1 trauma center by Nguyen et al found that positive THC screens were associated with improved survival after TBI [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased use of marijuana among Americans is coincided with its implication in emergency departments visits, motor vehicle collisions, and trauma [ 15 , 16 ]. THC has been associated with neuroprotective effects after TBI in several preclinical studies [ 17 , 18 ]. A 3-year retrospective review from a Level 1 trauma center by Nguyen et al found that positive THC screens were associated with improved survival after TBI [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the combinational use of curcumin and candesartan, an angiotensin II receptor blocker used for the treatment of hypertension, showed better antioxidative, antiapoptotic, and anti-inflammatory effects than curcumin or candesartan alone [ 89 ]. In addition, tetrahydrocurcumin, the metabolite of curcumin, could also alleviate brain edema and reduce neuronal cell apoptosis, as well as improve neurobehavioral function via the Nrf2 signaling pathway in weight drop-induced TBI mice [ 90 ]. Taken together, curcumin together with its metabolites are useful for the treatment of TBI.…”
Section: The Potential Therapy Of Phytochemicals As Nrf2 Activators I...mentioning
confidence: 99%
“…H 2 treatment improved BBB integrity, brain edema, and neurological performance in rats [ 201 - 204 ]. Other natural compounds and their effects are reported in Table 2 [ 205 - 231 ].…”
Section: Novel Pharmacologic Strategies For Tbi: From Experimental To...mentioning
confidence: 99%